Konsep Small Claim Procedure Untuk Menyelesaikan Perkara Perdata Permohonan (Volunter) Di Pengadilan Agama - Yaqin, Muharrom Ainul (Jurisdictie: Jurnal Hukum dan Syariah, 2015)
This article aims to formulate the concept of small claims procedure that can be used to check the examination of civil cases in the court petition religion, as well as describe the types of cases that can be checked by using a system of small claims procedure. The concept of small claims procedure can be applied in religious courts, to examine and decide cases petition (volunteer) with consideration of the substance of the case filed is simple. Nevertheless, the judges who hear cases iniharus memeliki experience and proficiency in handling the case of the petition. For the system to be enforced in court, this concept needs to be formulated in the form of Supreme Court Regulation. An application includes a simple matter if it has the value of materials or rights that are simple, the application is simple, and it is possible to be examined in one trial. Based on these criteria, there are eight types of cases that can be checked using a system of small claims procedure are: the permit application mating, pleas guardian adhol, request dispensation mating, pleas prevention marriage, request the establishment of origin of the child, the request istbat marriage, requesting to change the identity of marriage, and request the appointment of a guardian. Artikel ini bertujuan merumuskan konsep small claim procedure yang dapat digunakan untuk memeriksa pemeriksaan perkara perdata permohonan di pengadilan agama, serta mendeskripsikan jenis perkara yang dapat diperiksa dengan menggunakan sistem small claim procedure. Konsep small claim procedure dapat diterapkan di pengadilan agama, untuk memeriksa dan memutus perkara permohonan (volunter) dengan pertimbangan substansi perkara yang diajukan bersifat sederhana. Meskipun demikian, hakim yang memeriksa perkara iniharus memiliki pengalaman dan kecakapan dalam menangani perkara permohonan. Agar sistem ini dapat diberlakukan di pengadilan, konsep ini perlu dirumuskan dalam bentuk Peraturan Mahkamah Agung. Suatu permohonan termasuk perkara yang sederhana jika memiliki nilai materi atau hak yang sederhana, permohonannya sederhana, dan sangat memungkinkan untuk diperiksa dalam satu kali sidang. Berdasarkan kriteria tersebut, ada delapan jenis perkara yang dapat diperiksa menggunakan sistem small claim procedure yaitu: permohonan izin kawin, permohonan wali adhol, permohonan dispensasi kawin, permohonan pencegahan perkawinan, permohonan penetapan asal-usul anak, permohonan istbat nikah, permohonan perubahan identitas nikah, dan permohonan pengangkatan wali.